Status and Application of Information and Communication Technology (ICT) in Barun Multiple Campus (BMC), Khandbari - Dahal, Rudra Nath (BARUN Journal, 2025)
This chapter provides an overview of the Status and Application of Information and Communication Technology (ICT) at Barun Multiple Campus (BMC), Khandbari. With the rapid advancements in technology. integrating ICT into education and administration has become essential for enhancing teaching quality. streamlining administrative tasks, and developing a modern educational environment. Barun Multiple Campus, located in a rural region of Nepal, has been making efforts to incorporate ICT into its academic framework. Though challenges persist in terms of infrastructure and digital literacy. Barun Multiple Campus, a community-based institution in the eastern region of Nepal. acknowledges the growing importance of ICT in the educational sector. Given its rural location and resource limitations, the institution has faced barriers in fully leveraging technology for education. This chapter aims to evaluate the status of ICT at BMC and analyze its application in various academic and administrative domains. This study aims to evaluate the current state of ICT infrastructure and resources at BMC, assess the implementation and use of ICT in teaching and learning. investigate how ICT is applied in administrative activities, understand the level of ICT skills among faculty members and students, identify barriers to the effective adoption of ICT, and offer recommendations for enhancing ICT integration. The research follows a descriptive study design, collecting both qualitative and quantitative data. A combination of surveys, interviews, and document analysis was used. Questionnaires were distributed to the faculty, staff, and students, while interviews with administrative personnel provided additional insights into the ICT challenges and practices, Document reviews of campus policies and ICT related resources were conducted to understand the institutional approach towards technology integration. The basic ICT infrastructure is in place but insufficient to fully support all educational and administrative activities, while some faculties incorporate ICT in teaching. there is a need for further training and resources, and limited internet bandwidth, along with a lack of advanced ICT tools, hinders further progress. Although BMC has made strides in incorporating ICT. further investments and strategic planning are crucial for overcoming existing challenges and ensuring the effective use of ICT for educational and administrative advancement. This chapter concludes with recommendations for improving ICT infrastructure. Increasing faculty training and expanding the ICT curriculum.